PENGARUH PENGGUNAAN MEDIA 3 DIMENSI BERBASIS METODE DISKUSI TERHADAP HASIL BELAJAR PESERTA DIDIK PADA PEMBELAJARAN TEMATIK DI KELAS VI SD NEGERI 17 KAB. BARRU - Ningrum, Widya Sasmita; St. Syamsudduha; Muh. Anwar HM (Primer Edukasi Journal, 2025)
This research aims to: 1) Class VI thematic learning outcomes before using 3-dimensional media based on the discussion method, 2) Class VI thematic learning outcomes after using 3-dimensional media based on the discussion method, 3) How influential is the use of 3-dimensional media based on the discussion method on student learning outcomes in thematic learning in class VI. This research is a quasi-experimental research with a One-Group Pretest-Posttest Design. Data collection methods used in this study are tests and observations. To test the hypothesis using the paired sample t-test. Data analysis was carried out descriptively. The results of the descriptive analysis of the learning outcomes of class VI students at SD Negeri 17 Barru District before using 3-dimensional media based on the discussion method average grades obtained by students were 58.76, with a maximum score of 67 and a minimum of 52. Learning outcomes for class VI students at SD Negeri 17 Barru District after using 3-dimensional media based on the discussion method the average score obtained by students was 78.84, with a maximum score of 88 and a minimum of 73. Based on the results of the analysis above, it was hypothesized that the use of 3-dimensional media based on the discussion method had an effect on student learning outcomes in thematic learning in class VI of SD Negeri 17 Kab. Barru.